2010
DOI: 10.1007/s13237-010-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics of Astyanax ribeirae (Teleostei, Characidae), an endemic characin of the Atlantic rainforest

Abstract: Astyanax ribeirae is a characin fish endemic to Ribeira de Iguape river basin, Brazil. Karyotypic analysis of the specimen from distinct geographic regions depicted similar karyotypic features, i.e. 2n=50 constituting the 4 M+10SM+ 6ST+30A and a fundamental number (FN) equal to 70. Further analysis on linear differentiation using silver nitrate staining, c-banding and rDNA localization revealed single NOR on ST/A chromosomes, heterochromatin blocks in the pericentromeric region of some chromosomes, and four 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Although some Astyanax species, especially those collected at the Brazilian coast, present significant variation in the distribution of 5S rDNA [Kavalco et al, 2004[Kavalco et al, , 2010Vicari et al, 2008], both karyomorphs analyzed here showed similar distribution patterns for the smallest rRNA genes when compared to other A . fasciatus species and populations [Almeida-Toledo et al, 2002;Pazza et al, 2006;Peres et al, 2008;Hashimoto et al, 2011].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although some Astyanax species, especially those collected at the Brazilian coast, present significant variation in the distribution of 5S rDNA [Kavalco et al, 2004[Kavalco et al, , 2010Vicari et al, 2008], both karyomorphs analyzed here showed similar distribution patterns for the smallest rRNA genes when compared to other A . fasciatus species and populations [Almeida-Toledo et al, 2002;Pazza et al, 2006;Peres et al, 2008;Hashimoto et al, 2011].…”
Section: Discussionmentioning
confidence: 54%
“…The third chromosomal group is related to patterns of constitutive heterochromatin, mobile elements and rDNA distribution in the analyzed samples, which are distinct from those described for other Astyanax species and populations [Abel et al, 2006;Artoni et al, 2006;Medrado et al, 2008;Pazza et al, 2008;Peres et al, 2008]. In Astyanax , the constitutive heterochromatin distribution patterns have been considered a useful tool to analyze the karyotypic differentiation process Abel et al, 2006;Kavalco et al, 2010] and its influence on gene expression . Also, the occurrence of conspicuous heterochromatic blocks, mainly those on the terminal regions of subtelo-/acrocentric chromosomes, has been related to the presence of the As51 satellite DNA Pazza et al, 2008;Vicari et al, 2008], and such characteristics seem to be associated with the geographic location of the samples [Kavalco et al, 2013].…”
Section: Discussionmentioning
confidence: 92%
“…The clade 1 obtained by our molecular analyses corresponds to clade 5 of Rossini et al (2016) . In the specimens analyzed we can observe the plesiomorphic chromosome characteristics (as a karyotype with 2n = 50 chromosomes and a low FN) and with good structure in A. ribeirae ( Kavalco et al, 2010 ), A. intermedius , and A. giton ( Kavalco and Moreira-Filho, 2003 ; Kavalco et al, 2004 ). In A. hastatus , different cytotypes with 2n = 50 chromosomes have been observed, constituting yet another species complex within the genus Astyanax ( Kavalco et al, 2009 ), as corroborated by the present study ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 90%
“…Some chromosomes. 2 - 4 6 absent Kavalco et al (2010 ) Town of Sete Barras/SP Ribeira de Iguape river basin 50 4M+10SM+6ST+30A 70 Pericentromeric. Some chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some chromosomes. - 6 4 6 absent Kavalco et al (2010 ) D. taeniatus a Hydroelectric Risoleta Neves Reservoir/MG Doce river basin 50 14M+12SM+16ST+8A 92 Centromeric and pericentromeric. Most SM and ST. 4-8 - 10 8 - Da Cunha et al (2016 ) 50 10M+14SM+18ST+8A 92 Centromeric and pericentromeric.…”
Section: Introductionmentioning
confidence: 99%